Inflammatory Bowel Disease Therapeutics: A Focus on Probiotic Engineering - Jayshree Mishra; Madyson Stubbs; Longxiang Kuang; Nitza Vara; Priyam Kumar; Narendra Kumar (Hindawi Limited, 2022)
Inflammatory bowel disease (IBD) is a chronic inflammatory condition of gastrointestinal (GI) tract with dysregulated mucosal immune functions and disturbed commensal ecosystem of the intestinal lumen. IBD is categorized into two major subsets: Crohn's disease (CD) and ulcerative colitis (UC). Though advent of biologics has shifted the treatment with relatively longer remission compared to small molecule pharmaceuticals, patients still suffer from long-term complications. Since gut-microbiome is now accepted as another human organ holding potential for long-lasting human health, probiotics, and its engineering hold great promises to treat several previously untreatable chronic inflammatory conditions including IBD. Several emerging biological engineering tools have unlimited potential to manipulate probiotic bacterial system. These can produce useful therapeutic biologics with a goal to either ameliorate and/or treat previously untreatable chronic inflammatory conditions. As gut-microbiome is diverse and vary in different ethnic, geographic, and cultural human population, it will be important to develop vision for personalized probiotic treatment and develop the technology thereof to make personalized probiotic options a reality. The aim of this review paper is to present an overview of the current knowledge on both pharmacological and nonpharmacological IBD treatment modalities with a special emphasis on probiotic strains that are developed through the probiotic engineering. These engineered probiotics contain the most anti-inflammatory cytokines found within the human immune response and are currently being used to treat the intestinal inflammation in IBD for the IBD treatment.